Analisis Kinerja Keuangan Bank Umum BUMN Dengan Menggunakan Rasio Profitabilitas Tahun 2018-2022: Analisis Kinerja Keuangan Bank Umum BUMN Dengan Menggunakan Rasio Profitabilitas Tahun 2018-2022 - Agung Pramayuda; Retno Widya Ningrum, Retno Widya Ningrum; Irfan Achmad Musadat, Irfan Achmad Musadat (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Banking financial performance includes a number of indicators used to evaluate whether a financial institution is healthy or not. Financial performance refers to the evaluation and analysis of financial performance. Evaluation of financial performance involves a number of financial indicators and ratios that provide an overview of the company's condition. The financial sector, especially banking, has a very important role in supporting economic growth in Indonesia. Analysis of financial performance in commercial banks of BUMN uses ratios. profitability, which is one of the ratios used to determine the effectiveness of the company's assets and capital to generate profits which have an impact on the company's financial performance. In the profitability ratio in question, the author uses the Net Interest Margin (NIM), Return On Asset (ROA) and Return On Equity (ROE) ratios. Based on the results of the discussions that have been carried out, in general the financial performance commercial banks of BUMN for the 2018-2022 period, seen from profitability ratios, shows quite good financial performance, this is assessed from the achievement of NIM, ROA and ROE ratios which show positive numbers. This means that the company still generates profits by optimizing the assets and capital it owns. Apart from that, the NIM value shows a positive ratio, meaning that the company has bank interest income that is greater than the interest costs incurred.